2017
DOI: 10.1002/etc.3846
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive characterization of the acute and chronic toxicity of the neonicotinoid insecticide thiamethoxam to a suite of aquatic primary producers, invertebrates, and fish

Abstract: Thiamethoxam is a neonicotinoid insecticide used widely in agriculture to control a broad spectrum of chewing and sucking insect pests. Recent detection of thiamethoxam in surface waters has raised interest in characterizing the potential impacts of this insecticide to aquatic organisms. We report the results of toxicity testing (acute and chronic) conducted under good laboratory practices for more than 30 freshwater species (insects, molluscs, crustaceans, algae, macrophytes, and fish) and 4 marine species (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 23 publications
1
50
4
1
Order By: Relevance
“…When compared with neonicotinoids in North American surface water samples, the risk was found to be low, with a likelihood of ∼0.5% of exceeding the HC5. In contrast to these studies, an earlier assessment by Morrissey et al derived an HC5 of 0.63 μg L − 1 , which is lower than the results shown in the present study and by others (Finnegan et al ; Whitfield‐Aslund et al ).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…When compared with neonicotinoids in North American surface water samples, the risk was found to be low, with a likelihood of ∼0.5% of exceeding the HC5. In contrast to these studies, an earlier assessment by Morrissey et al derived an HC5 of 0.63 μg L − 1 , which is lower than the results shown in the present study and by others (Finnegan et al ; Whitfield‐Aslund et al ).…”
Section: Resultscontrasting
confidence: 99%
“…A recent probabilistic ecological risk assessment for imidacloprid by Whitfield-Aslund et al (2017), which considered both acute lethal and immobility data, derived an acute HC5 of 1.73 mg active ingredient L À1 ; when compared with exposure distributions for multiple use patterns, they categorized the risk to aquatic invertebrates as de minimis. Similarly, Finnegan et al (2017) constructed an acute SSD for thiamethoxam and derived HC5s of 5.1 and 22.9 mg L À1 using EC50s and LC50s, respectively. When compared with neonicotinoids in North American surface water samples, the risk was found to be low, FIGURE 2: Species sensitivity distributions (SSDs) of acute ( 5 d) toxicity data for 6 neonicotinoids constructed using median lethal concentration (LC50) values for aquatic invertebrates generated from the present study and external literature data mined from the ECOTOX database.…”
Section: Hazard Assessmentmentioning
confidence: 99%
“…Such differences are evident with neonicotinoids: both our study and that of Crosby et al (2015) found significant effects, but others did not (Finnegan et al 2017;Miles et al 2017). No sublethal effects on swimming behavior, feeding activity, or reactions to an external stimulus were detected during acute and chronic exposures of rainbow trout (Oncorhynchus mykiss) to thiamethoxam (maximum concentration tested was 100 mg/L; Finnegan et al 2017). No sublethal effects on swimming behavior, feeding activity, or reactions to an external stimulus were detected during acute and chronic exposures of rainbow trout (Oncorhynchus mykiss) to thiamethoxam (maximum concentration tested was 100 mg/L; Finnegan et al 2017).…”
Section: Discussioncontrasting
confidence: 60%
“…The reference Ashwell and Dark (2002) a Acute and chronic endpoints were based on evaluation of data summarized by Finnegan et al (2017). Average daily biomass for the diatoms ranged from 0.05 to 4.47 g C/m 2 .…”
Section: Resultsmentioning
confidence: 99%